2012
DOI: 10.1111/j.1530-0277.2012.01877.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of l‐Cysteine on Reinstatement of Ethanol‐Seeking Behavior and on Reinstatement‐Elicited Extracellular Signal–Regulated Kinase Phosphorylation in the Rat Nucleus Accumbens Shell

Abstract: Altogether, these results indicate that L-cysteine could be an effective pharmacological agent for the prevention of behavioral and molecular correlates of EtOH-primed reinstatement of EtOH seeking and that the shell of the Acb represents a critical neural substrate for priming-elicited reinstatement mechanisms involving ERK phosphorylation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…In addition, a wealth of experimental evidence supports that the motivational effects of ethanol are mediated by its metabolism into ACD either in the periphery or in the brain. Accordingly, this has been demonstrated by inhibiting the production of ACD in the periphery (inhibition of ADH), by inhibiting the generation of brain ACD (inhibition of brain catalase) or by reducing ACD bioavailability (Font et al, 2006a,b; Peana et al, 2008a, 2009, 2010a, 2013a,b; Enrico et al, 2009; Sirca et al, 2011; Correa et al, 2012). All these observations support the tenet that the generation of central and peripheral, but not peripherally accumulated (Escrig et al, 2012), ACD actively participates in the positive motivational properties of ethanol and raise the possibility that its role can be exploited to devise novel pharmacological approaches that target alcohol abuse related problems.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, a wealth of experimental evidence supports that the motivational effects of ethanol are mediated by its metabolism into ACD either in the periphery or in the brain. Accordingly, this has been demonstrated by inhibiting the production of ACD in the periphery (inhibition of ADH), by inhibiting the generation of brain ACD (inhibition of brain catalase) or by reducing ACD bioavailability (Font et al, 2006a,b; Peana et al, 2008a, 2009, 2010a, 2013a,b; Enrico et al, 2009; Sirca et al, 2011; Correa et al, 2012). All these observations support the tenet that the generation of central and peripheral, but not peripherally accumulated (Escrig et al, 2012), ACD actively participates in the positive motivational properties of ethanol and raise the possibility that its role can be exploited to devise novel pharmacological approaches that target alcohol abuse related problems.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, previous findings have reported that intracerebroventricular the structural analogue of L-cysteine, D-penicillamine, reduces voluntary ethanol consumption in rats indicating that the central inactivation of ACD also blocks ethanol intake (Font et al, 2006b). On the other hand, L-cysteine reduces the acquisition and maintenance of oral ethanol self-administration as well as the reinstatement of ethanol-drinking and ethanol-seeking behaviors (Peana et al, 2010a, 2013a). Others studies examined the motivational effects of ACD under the break point that serves as an index of animals' motivation to work for the reinforcer.…”
Section: Conditioned Place Preference and Self-administration Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A rapidly growing body of evidence on the efficacy of radical scavengers and antioxidants such as L-cysteine (Peana et al, 2010a, 2012, 2013b), alpha lipoic acid (Ledesma et al, 2012; Peana et al, 2013a) and N-acetyl cysteine (Quintanilla et al, 2016), both on CPP experiments and in different phases (not only during the acquisition) of operant self-administration as well as on voluntary ethanol intake could be referred to the observation that a neuro-inflammatory process could be responsible of ethanol excessive taking (Montesinos et al, 2016). Indeed, the metabolism of ethanol into acetaldehyde and acetate is associated to the production of ROS that accentuate the oxidative state of cells promoting oxidative damage, neuronal injury and neurodegeneration.…”
Section: Neurobiological Effects Of Ethanol and Role Of Acetaldehydementioning
confidence: 99%
“…After extinction from EtOH SA, systemic mGluR5 inhibition attenuated cue-induced reinstatement and the cue-induced pERK expression in the BLA and NAc shell in alcohol-preferring rats 257 . Probably through restoring the Glu transmission, L-cysteine prevents EtOH SA and EtOH-primed-induced drug seeking 258 . In addition, the reinstatement-induced pERK in the NAc shell is also inhibited by the L-cystine pre-treatment.…”
Section: Erk Signaling and Drug Addictionmentioning
confidence: 99%